Time course of red blood cell intracellular pH recovery following short-circuiting in relation to venous transit times in rainbow trout, Oncorhynchus mykiss - Harter, Till S. (Am J Physiol Regul Integr Comp Physiol, 2018)
Accumulating evidence is highlighting the importance of a system of enhanced hemoglobin-oxygen (Hb-O(2)) unloading for cardiovascular O(2) transport in teleosts. Adrenergically stimulated sodium-proton exchangers (β-NHE) create H(+) gradients across the red blood cell (RBC) membrane that are short-circuited in the presence of plasma-accessible carbonic anhydrase (paCA) at the tissues; the result is a large arterial-venous pH shift that greatly enhances O(2) unloading from pH-sensitive Hb. However, RBC intracellular pH (pH(i)) must recover during venous transit (31–90 s) to enable O(2) loading at the gills. The halftimes (t(1/2)) and magnitudes of RBC β-adrenergic stimulation, short-circuiting with paCA and recovery of RBC pH(i), were assessed in vitro, on rainbow trout whole blood, and using changes in closed-system partial pressure of O(2) as a sensitive indicator for changes in RBC pH(i). In addition, the recovery rate of RBC pH(i) was assessed in a continuous-flow apparatus that more closely mimics RBC transit through the circulation. Results indicate that: 1) the t(1/2) of β-NHE short-circuiting is likely within the residence time of blood in the capillaries, 2) the t(1/2) of RBC pH(i) recovery is 17 s and within the time of RBC venous transit, and 3) after short-circuiting, RBCs reestablish the initial H(+) gradient across the membrane and can potentially undergo repeated cycles of short-circuiting and recovery. Thus, teleosts have evolved a system that greatly enhances O(2) unloading from pH-sensitive Hb at the tissues, while protecting O(2) loading at the gills; the resulting increase in O(2) transport per unit of blood flow may enable the tremendous athletic ability of salmonids.